Absence of the lateral and third ventricles associated with holoprosencephaly - Ciftcioglu, Engin (Anat Cell Biol, 2015)
We describe a 6-month-old boy suffering from motor and mental retardation. All radiological features were suggestive of holoprosencephaly with no identifiable lateral or third ventricles and fusion of the thalami.